Project Based Learning dalam Pembelajaran Matematika - Rissa Azizah (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2022)
Problem Based Learning (PjBL) is student-centered learning that is used to develop active and in-depth learning by engaging students in investigating real-world problems in a collaborative environment. The writing of this article uses the method of literature review from books, articles and journals published in the last ten years. This paper will discuss how PjBL is implemented. Based on the literature review, this paper also discusses the characteristics of PjBL, implementation of PjBL, advantages and challenges of PjBL, technical guidelines for implementing PjBL. From the student's point of view, PjBL provides useful insight into the process of assessment, field work and group exercises, motivating students and making subject matter more interesting. From the teacher's perspective, the challenges in implementing PjBL are workload, teacher's knowledge of material content, lack of experience of teachers and students, and the need to develop materials for learning outside the classroom.